(untitled) (Research, Society and Development, 2021)
Worldwide, colorectal cancer is considered the most fatal and the second leading cause of cancer death. Factors such as population aging and lifestyle habits are related to the prevalence of this cancer. This review article aims to expose, through the analysis of scientific articles, the importance of early diagnosis in patients with risk factors for colorectal cancer. This is a systematic qualitative bibliographic review carried out between the years 2018 to 2021 in Portuguese, English and Spanish. Epidemiological data reinforce the importance of cancer screening, mainly due to the increase in RCC cases in the last 30 years. This reality is attributed to environmental factors, mainly related to lifestyle (sedentary lifestyle, malnutrition, obesity, smoking) and population aging. Therefore, screening is based on risk factors. Screening should start at age 45, as early detection of CCR can significantly reduce mortality rates. Colorectal cancer is considered one of the most prevalent neoplasms in the world. Previously it was more common in patients over the age of 50 years, but this reality has changed due to the lifestyle of the population. Unfortunately, there is no screening for this type of cancer that is offered by the Unified Health System (SUS) and, therefore, early diagnosis does not occur as often as expected. . It is necessary to develop forms of screening for this cancer, as well as those carried out in breast and prostate cancer, since colorectal cancer is aggressive and has high mortality rates.